2000
DOI: 10.2176/nmc.40.484
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Intracranial Hypotension Associated With Bilateral Chronic Subdural Hematomas. Case Report.

Abstract: A 34-year-old female presented with spontaneous intracranial hypotension (SIH) manifesting as severe postural headache and meningism. Magnetic resonance (MR) imaging with gadolinium showed diffuse pachymeningeal enhancement. She developed bilateral chronic subdural hematomas 4 weeks after the onset of the symptoms. MR imaging showed descent of the midline structures of the brain. The bilateral chronic subdural hematomas were surgically drained, with no remarkable pressure. Postoperative MR imaging showed compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…4 8 A review of published reports revealed a few cases of SIH complicated by small subdural collections which required neurosurgical drainage. [9][10][11][12][13][14] However, there are no records of large subdural haematomas causing a decreased conscious level and requiring urgent neurosurgical drainage. This study was undertaken to assess the incidence of this serious complication of SIH.…”
mentioning
confidence: 99%
“…4 8 A review of published reports revealed a few cases of SIH complicated by small subdural collections which required neurosurgical drainage. [9][10][11][12][13][14] However, there are no records of large subdural haematomas causing a decreased conscious level and requiring urgent neurosurgical drainage. This study was undertaken to assess the incidence of this serious complication of SIH.…”
mentioning
confidence: 99%
“…Standard approaches include craniostomy by either burr hole or twist drill, evacuation of the hematoma with or without irrigation and in most instances drainage. Defenders of drainage argued that this latter will allow brain expansion by progressive evacuation of residual fluid after spontaneous evacuation or irrigation of the cavity; also it seems to diminish early complications (42,44,(46)(47)(48)(50)(51)(52). Since the mid of the 80's, all series reporting treatment with drainage used a system of closed-drainage.…”
Section: Discussionmentioning
confidence: 99%
“…The most surgical techniques used are craniostomy by burr hole or twist drill with or without irrigation, and with or without drainage (2,4,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Drainage seems to be a must for several authors (42,(44)(45)(46)(47)(48)(49)(50)(51)(52). Closed system drainage is used since the mid of the 80's because open drainage had been incriminated in high rates of infection (53)(54)(55)(56).…”
Section: Background and Importancementioning
confidence: 99%
“…Certain pre-morbid conditions, i.e. sufficient potential subdural space such as arachnoid cyst, brain atrophy, or intracranial hypotension with or without head injury, 13,19,22) are prerequisites for the occurrence of CSDH. Unresolved subdural hygroma with or without blood induces proliferation of dural border cells by evoking inflammatory reaction and production of neomembranes.…”
Section: Discussionmentioning
confidence: 99%